Perkembangan publikasi internasional bidang pemantauan radiasi tahun 2011-2019 melalui basisdata Scopus - Noeraida Noeraida (Perpustakaan Universitas Gadjah Mada, 2020)
Introduction. There has been rapid development in radiation research. The purpose of the study is to understand the development of publications, researchers, institutions, countries, level of productivity and widely cited journals, knowledge mapping, researcher collaborations, and Indonesian researcher publications. Data Collection Method. This paper used a bibliometric analysis with a quantitative approach, by using Scopus data from 2011 to 2019, mapped by VOSviewer. Data Analysis. The analysis was performed by tabulating data using Microsoft Excel to produce rankings in accordance to the research objectives. Mapping analysis of bibliographic data was performed to provide co-occurrence of index keywords, and co-authorship of authors. Descriptive analysis was conducted to explain the results. Results and Discussion. The number of publications and citations per year increases with ratio 1: 6. Japan as the highest institution and country cited, dominates productive researchers with Onda Y as one top researcher. The highest cited journal publishing radiation monitoring research is the Journal of Environmental Radioactivity. The highest referenced document is written by Halliburton from the USA. The most popular topics of discussion are reactor accidents, nuclear power plants and radiation therapy. There are not many publications by Indonesian researchers indexed on Scopus. Conclusions. Japan has the most developed, productive and popular publications. Japanese researchers and institutions are widely used a reference globaly in the field of nuclear and radiation.